The experiences of police officers presenting with the symptoms of depression within the Gauteng South African Police Services (SAPS) - Motileng, B.B. (Barnard Buti) (University of Pretoria, 2023)
Mini Dissertation (MA (Research Psychology))--University of Pretoria, 2023.